2020
DOI: 10.1371/journal.pone.0231888
|View full text |Cite
|
Sign up to set email alerts
|

Reinforced education improves the quality of bowel preparation for colonoscopy: An updated meta-analysis of randomized controlled trials

Abstract: Background and aims Inadequate bowel preparation (BP) is an unfavorable factor that influence the success of colonoscopy. Although standard education (SE) given to patients are proved useful to avoid inadequate BP. Studies concerning the effects of reinforced education (RE) on the quality of BP were inconsistent. The aim of this updated meta-analysis of randomized controlled trial was to compare the quality of BP between patients receiving RE in addition to SE and those receiving SE alone. Methods MEDLINE, EMB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 49 publications
2
15
1
11
Order By: Relevance
“…Patient education is key to attaining good quality bowel preparation. 26 Our meta-analysis shows that adjuncts can be used with bowel preparation in a safe manner without compromising mucosal visualisation but, conversely, increase bowel cleanliness by enhancing palatability and tolerability. This may have implications for the patient perception of colonoscopy and may improve compliance with colonoscopy attendance.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Patient education is key to attaining good quality bowel preparation. 26 Our meta-analysis shows that adjuncts can be used with bowel preparation in a safe manner without compromising mucosal visualisation but, conversely, increase bowel cleanliness by enhancing palatability and tolerability. This may have implications for the patient perception of colonoscopy and may improve compliance with colonoscopy attendance.…”
Section: Discussionmentioning
confidence: 80%
“…Many patients and healthcare professionals hold the misconception that bowel preparation should only be used with water. Patient education is key to attaining good quality bowel preparation 26 . Our meta‐analysis shows that adjuncts can be used with bowel preparation in a safe manner without compromising mucosal visualisation but, conversely, increase bowel cleanliness by enhancing palatability and tolerability.…”
Section: Discussionmentioning
confidence: 91%
“…Our pooled analysis shows that supplementary education based on traditional nursing education can significantly improve the rate of adequate bowel preparation (79.9% vs 72.9, p <0.00001) for outpatients. A recent meta-analysis showed that reinforced education based on standard education improves the quality of bowel preparation for colonoscopy [ 40 ]. Unlike this study, we only explored the effect of supplemental education on the quality of bowel preparation in outpatients.…”
Section: Discussionmentioning
confidence: 99%
“…La incidencia de inadecuada preparación fue del 10 % en los pacientes evaluados, a diferencia de lo estimado en otros estudios, alrededor del 20 %-40 % (21,22) . Esta diferencia puede deberse a la educación individualizada que se ofrece a los pacientes durante la asignación de la cita y dos días previos al procedimiento (23,24) . Los pacientes con mala preparación fueron principalmente mujeres (59 %) y personas menores de 60 años (68 %), lo cual controvierte algunos factores predictores de mala preparación reportados recientemente (21,25,26) .…”
Section: Discussionunclassified